Biotransformation of Myricetin: A Novel Metabolic Pathway to Produce Aminated Products in Mice. Issue 14 (21st May 2019) - Zhang, Shuwei; Wang, Ronghui; Zhao, Yantao; Tareq, Fakir Shahidullah; Sang, Shengmin
Abstract : Scope: In this study, whether amination is a novel metabolic pathway of myricetin, one of the major dietary flavonoids found in fruits, vegetables, and tea, and whether the aminated metabolite of myricetin remains bioactive, are investigated. Methods and results: It is found that myricetin with a vic ‐trihydroxyl group on the B ring can chemically react with ammonia via the formation of myricetin quinone to generate the aminated product in vitro. As expected, the amination occurs on position 4´ of the B‐ring of myricetin. The structure of this new product is confirmed by 1D and 2D nuclear magnetic resonance (NMR) spectroscopy and liquid chromatography‐mass spectrometry and is named 4´‐NH2 ‐myricetin. Using the synthetic 4´‐NH2 ‐myricetin as a standard, the presence of this compound is searched for in fecal samples collected from myricetin‐treated mice using LC–MS, and 4´‐NH2 ‐myricetin is confirmed as the metabolite of myricetin in mice for the first time. Furthermore, two metabolites of myricetin, the mono‐methylated myricetin and the microbial‐derived metabolite 3, 4, 5‐trihydroxyphenylacetic acid, are confirmed to be aminated in vivo based on LC–MS data analysis. After administration of different doses of myricetin through oral gavage, the amination of myricetin shows a dose‐dependent response in feces. A similar trend is observed for the amination of the mono‐methylated myricetin, but not for the microbial‐derived metabolite 3, 4, 5‐trihydroxyphenylacetic acid. In plasma, the trend of a dose‐dependent response for the amination of myricetin and its mono methylated metabolite is observed, and the plasma concentration of the aminated 3, 4, 5‐trihydroxyphenylacetic acid at 200 mg kg –1 dose is significantly higher than those at the 100 and 400 mg kg –1 doses. Interestingly, it is observed that the aminated myricetin retains the anti‐inflammatory activity of myricetin. Conclusion: This result demonstrates that amination is a novel biotransformation mechanism of myricetin to produce aminated metabolites. Abstract : Myricetin is one of the major dietary flavonoids found in fruits, vegetables, and tea. The metabolic fate of myricetin is still largely unknown. This study demonstrates that amination is a novel biotransformation mechanism of myricetin to produce bioactive aminated metabolites.